Implementation of the Pharmacists’ Patient Care Process in a Medicinal Chemistry Course - Alsharif, Naser Z. (Am J Pharm Educ, 2020)
Objective. To implement the Pharmacists’ Patient Care Process (PPCP) in a medicinal chemistry course. Methods. Doctor of Pharmacy students in a medicinal chemistry course were challenged to apply the PPCP in a lesson on cholinesterase inhibitors and NMDA receptor antagonist in the treatment of Alzheimer’s disease. A clinical faculty member with expertise in the topic reviewed the clinical information provided to ensure applicability to patient care. A pre- and post-course survey was administered to assess students’ understanding of the PPCP and the effectiveness of the strategies used. Students’ pre- and post-course responses were analyzed, and qualitative themes were identified. Results. Of the 141 students enrolled in the course, 96% and 97% completed the pre- and post-course surveys, respectively. Students’ post-course responses were higher than pre-course answers to the question that they knew all the steps of the PPCP (96% vs 66%, respectively). Ninety one percent in the post-course survey compared to 62% in the pre-course survey listed the PPCP steps correctly. In addition, more than 90% of the students indicated that the strategies used in the class helped them understand and relate to the PPCP. Qualitative responses revealed themes with positive responses related to the course, course activities, PPCP goals and curriculum design based on the implementation of the PPCP. Conclusion. The introduction of the PPCP as a framework for all pharmacy practitioners is a worthy endeavor. Purposeful strategies to introduce the PPCP in a medicinal course were positively received by students. Formalized efforts to implement the PPCP in clinical, social and administrative, and science courses are critical to introduce the PPCP as a framework for all future pharmacy practitioners.